Modeling the impact of mentoring on women's work-life balance: A grounded theory approach - Parvaneh Bahrami; Saeed Nosratabadi; Khodayar Palouzian; Szilárd Hegedűs (Administrative Sciences, 2023)
The purpose of this study was to model the impact of mentoring on women's work-life balance. Indeed, this study considered mentoring as a solution to create a work-life balance of women. For this purpose, semi-structured interviews with both mentors and mentees of Tehran Municipality were conducted and the collected data were analyzed using constructivist grounded theory. Findings provided a model of how mentoring affects women's work-life balance. According to this model, role management is the key criterion for work-life balancing among women. In this model, antecedents of role management and the contextual factors affecting role management, the constraints of mentoring in the organization, as well as the consequences of effective mentoring in the organization are described. The findings of this research contribute to the mentoring literature as well as to the role management literature and provide recommendations for organizations and for future research.
Keywords: 350; grounded theory; mentoring; role management; women studies; work-life balance